Implementing allied healthcare professionals in transitional care for older adults with mental health needs: A scoping review - Marina Motsenok; Ella C.N. Wong; Rozhannaa Sothilingam; Monica Antunes; Catherine Devion; Emma Wilson; Amanda Knoepfli; Emma Elliot; Tracey DasGupta; Naomi Ziegler; Sander L. Hitzig (PLoS ONE, 2026)
Introduction Older adults experience several transitions in care, which can be challenging and stressful. Transitional care ensures continuity of care by addressing patients’ healthcare needs before discharge and providing ongoing community support. Although transitional care improves patient outcomes and reduces hospital readmissions, its role in addressing mental health (MH) needs in older adults remains underexplored. This scoping review describes the literature on the integration of allied healthcare (AHC) professionals in transitional care for older adults with MH needs. Method Following PRISMA-ScR guidelines, we analyzed 14 peer-reviewed articles (2010–2024) on transitions for older adults with cognitive impairment, dementia, depression, or suicide risk. Thematic analysis identified key roles, lessons, and patient needs in transitional care provided by AHC professionals. Results AHC professionals, including social workers, occupational therapists, pharmacists, and physical therapists, contributed through discharge planning, physiotherapy, medication reviews, MH counseling, and resource navigation. For caregivers, they provided education on dementia care, behavior management, and psychosocial support, improving caregiver well-being and interactions with persons with dementia. Transitional care interventions reduced caregiver stress and, in some cases, hospital readmissions. Challenges included suboptimal medication management for persons with dementia. Key facilitators were flexible delivery methods (e.g., telehealth), tailored interventions, and dementia-specific education. Conclusion AHC professionals are vital to transitional care for older adults with MH needs, offering tailored support to patients and caregivers. Enhanced integration, interdisciplinary collaboration, caregiver education, and addressing systemic barriers could improve care quality. Future research should focus on standardizing interventions and optimizing medication management.